The Impact of Business Support Services for Small and Medium Enterprises on Firm Performance in Low‐ and Middle‐Income Countries: A Systematic Review. Issue 1 (4th January 2016) - Piza, Caio; Cravo, Tulio Antonio; Taylor, Linnet; Gonzalez, Lauro; Musse, Isabel; Furtado, Isabela; Sierra, Ana C.; Abdelnour, Samer
Abstract : This Campbell systematic review assesses the effects of business support services in low‐ and middle‐income countries on firm performance and economic development. The review summarizes findings from 40 studies. Included studies examine interventions targeted at SMEs (two to 250 employees) involving tax simplification, exports and access to external markets; support for innovation policies; support to local production systems; training and technical assistance, and SME financing and credit guarantee programmes. Findings from 40 studies are summarised in the review. These studies present evidence from 18 low‐ and middle‐income countries, with 26 studies analysing programmes in Latin America, six from Asia and five from Africa. On average, business support to SMEs improves their performance, their ability to create jobs, their labour productivity and their ability to invest. The effects on innovation are unclear. Matching grants, technical assistance and tax simplification programmes improve firms' performance and job creation; with technical assistance also improving labour productivity. Export promotion and innovation programmes positively affect exports and innovation, but there is no evidence that they improve performance or job creation. However, the effects of the programmes studied are not very large. Most studies do not include the required data to assess if the programmes are cost effective. Plain language summary: BUSINESS SUPPORT SERVICES TO SMALL AND MEDIUM ENTERPRISES SEEM TO IMPROVE FIRM PERFORMANCE: The Campbell review in brief: Support to small and medium enterprises (SMEs) can improve their revenue and profits, their ability to create jobs, labour productivity and their ability to invest. But these effects are not large, and the cost effectiveness of the interventions not known. The effects on innovation are unclear. What is this review about?: Large amounts of funding are going towards programmes to support small and medium enterprises (SMEs) in low‐ and middle‐income countries in order to increase revenue and profits, generate employment, and, so, create economic growth and reduce poverty. The Campbell review summarizes evidence of the impact of these programmes on measures of SME performance including revenues, profits, and productivity, as well as the firms' ability to generate employment and their labour productivity. What are the main findings of this review?: What studies are included?: Included studies examine interventions targeted at SMEs (two to 250 employees) involving tax simplification, exports and access to external markets; support for innovation policies; support to local production systems; training and technical assistance, and SME financing and credit guarantee programmes. What is the aim of this review? This Campbell systematic review assesses the effects of business support services in low‐ and middle‐income countries on firm performance and economic development. The review summarizes findings from 40 studies. Findings from 40 studies are summarised in the review. These studies present evidence from 18 low‐ and middle‐income countries, with 26 studies analysing programmes in Latin America, six from Asia and five from Africa. Do business support services work?: On average, business support to SMEs improves their performance, their ability to create jobs, their labour productivity and their ability to invest. The effects on innovation are unclear. Matching grants, technical assistance and tax simplification programmes improve firms' performance and job creation; with technical assistance also improving labour productivity. Export promotion and innovation programmes positively affect exports and innovation, but there is no evidence that they improve performance or job creation. However, the effects of the programmes studied are not very large. Most studies do not include the required data to assess if the programmes are cost effective. What do the results mean?: Overall SME support has a positive impact on various measures of firm performance, but with some caveats. Results for all the interventions studied could not be provided due to a lack of evidence. And the evidence available was mainly about programmes in Latin American countries. There is a likelihood of bias in many studies. Most did not report programme implementation costs, so it is not possible to weigh costs against benefits. Research on these programmes in sub‐Saharan Africa in particular should be prioritised, as this would contribute to the understanding of the role that support to small businesses may play in development processes there. Abstract: BACKGROUND AND OBJECTIVES OF THE REVIEW: Business support interventions in low and middle‐income countries (LMICs) direct a large amount of resources to SMEs, with the assumption that institutional constraints impede small and medium‐sized enterprises (SMEs) from generating profits and employment at the firm level, which in turn is thought to impede economic growth and poverty reduction. Yet despite this abundance of resources, very little is known about the impact of such interventions. To address this gap, this systematic review analyses evaluations of SME support services in LMICs to help inform policy debates pertaining to SMEs and business support services. This review examines the available evidence on the effects of SME support services in LMICs on firm‐level performance indicators (such as revenues, profits, and productivity), employment generation, and labour productivity. METHODS: We systematically searched for available literature. To identify relevant papers for this review, we conducted electronic searches on key platforms; snowball sampling of references from relevant papers and book chapters, and suggestions from recognized experts in the field. We focused on LMICs as defined by the World Bank classifications, and on evidence published since the year 2000, so as to include more sophisticated evaluation techniques. The references retrieved for this review are up‐to‐date as of December 2014. We included studies that evaluated the effectiveness of business support services on firm level outcomes of SMEs in low‐ and middle‐income countries. We defined SMEs as firms with between two and 250 employees, but also included studies that used annual revenue to classify firms as SMEs instead of employee count. We examined interventions involving tax simplification, exports and access to external markets; support for innovation policies; support to local production systems; training and technical assistance, and SME financing and credit guarantee programmes. We looked at studies documenting the impact of any business support service on SMEs when compared with business as usual. We included studies that report at least one final outcome of interest (such as higher profits, employment generation, and productivity). We incorporated studies that use experimental and quasi‐experimental methods, and other studies purporting to control for selection bias and endogeneity in selection into the programme. The search results were screened by two review researchers, and the included studies were similarly coded by two researchers. This double‐review process was designed to make the selection procedure and coding more rigorous and to screen for mistakes. We coded the data according to the impacts and characteristics of the studies selected. Standardised mean difference was used to code continuous variable outcomes and risk ratios to code binary variables outcomes. Effect sizes were synthesised and summarised to one effect size per outcome per study. Given the heterogeneity of true effects, we used analyses of random effects models to estimate overall average standardised effects. Moderator analysis was conducted with four additional variables. RESULTS: The initial search returned 9, 475 studies, which after dropping duplicates and applying the selection criteria were reduced to a final sample of 40 studies. These consisted of 37 papers (23 peer reviewed and 20 working papers), and 6 book chapters. All were produced between 2003 and 2014. Four of these studies could not be included in the meta‐analysis as incomplete information prevented us from computing standardised measures. The review reports 242 effect sizes (ES), and the meta‐analysis is based on 72 ES; 64 continuous and eight binary outcomes. Overall, our findings indicate that: Business support to SMEs improves firms' performance (average ES of 0.13 standard deviations (SD) and confidence interval (CI) (0.06, 0.20)), helps create jobs (average ES of 0.15 SD and CI (0.08, 0.22)), has a positive effect on labour productivity (average ES of 0.11 SD and CI (0.08, 0.15)), on exports (average ES of 0.04 and CI (0.01, 0.06)) and on firms' investment (average ES of 0.13 SD and CI (0.02, 0.24)). Evidence on their effects on innovation by SMEs is less clear (average ES of 0.05 SD and CI (‐0.01, 0.12). When the analysis is disaggregated by type of intervention, we find that matching grants continue to show a positive impact on firms' performance and employment of similar magnitude and precision once we exclude some outliers. Excluding the outliers, the average ES for these two outcomes are 0.15 SD (with CI (0.08, 0.22)) and 0.14 SD (with CI (0.03, 0.24)) respectively. Even though they are based on only few studies, results from meta‐regression indicate that technical assistance programmes have some positive effects on firms' performance, jobs creation and labour productivity, whereas tax simplification programmes seem to improve firm performance and generate jobs. Export promotion and innovation programmes seem to positively affect exports and innovation respectively, but do not seem to have an effect firm performance and employment creation outcomes. The average ES are extremely low and very imprecisely estimated. IMPLICATIONS FOR POLICY AND RESEARCH: Our findings suggest that, overall, SME support has a positive impact on firm performance indicators. The results of our review should not be interpreted as clear evidence of SME support effectiveness, however, as the meta‐analysis was unable to provide results for all types of interventions or for specific countries. There was also significant risk of bias in many studies. Most of the studies found relate to Latin America, and thus cannot be interpreted as being applicable to other regions, including Africa. We recommend further analysis of cost‐effectiveness, as most studies do not indicate the cost of implementation. There remains a paucity of rigorous evaluation studies on SME support programmes in Africa, and Sub‐Saharan Africa in particular. Therefore, the generation of more evidence for the African context is paramount to the improved understanding of the role SME support programmes might play in the development process.